(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
This article analyzes the process of transformation of cultural values in the society of New Uzbekistan from a scientific and theoretical perspective. It examines the concept of cultural values, their role in social development, the substantive changes occurring during the reform period, and the impact of globalization and the digital environment. The study also highlights the modern interpretations of traditional values, the role of civil society institutions, and the significance of youth in this process. The article argues that the renewal of cultural values is not a rejection of tradition, but rather a process of continuous development and harmonization